Analisis Faktor Kesulitan Dalam Memahami Kaidah Bahasa Arab Siswa Kelas VI B SDIKT Robbi Rodhiya - Salamah, Nur; Mahardini, Angger Putri; Rahmawati, Rima Ajeng (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
This research is motivated by students' difficulties in understanding Arabic rules both from internal and external factors. The purpose of this research is to find out the students' abilities and their difficulties in understanding Arabic rules, especially in fi'il material in terms of time and era. This subject was a class VI B student at SDIKT Robbi Rodhiya with a total of 29 students and 16 students who were the source of data in this study who still had difficulty understanding the material. Data collection techniques for this study used observation, interviews, documentation and test questions. While the data analysis technique uses data reduction, data presentation and drawing conclusions